Use of one lung ventilation during repair of oesophageal atresia (OA) with tracheoesophageal fistula (TOF) in neonates to improve survibility - Bhowmick, Dilip Kumar; Isa, M; Paul, M; Ali, M; Islam, K; Hoque, AKM Faizul (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Background Oesophageal atresia (OA) and tracheo-oesophageal fistula (TOF) is one of the surgical emergencies in newborn. Survival rate after corrective surgery is not encouraging in our country. Objective To describes a new technique of airway and ventilatory management during surgical repair of oesophageal atresia and tracheo-oesophageal fistula in neonates. Methods A total number of 12 neonates both male (10) and female (02) with Type- C oesophageal atresia have been operated to correct the anomaly since 2007. The patient’s age range was 1 to 17 days, weighing 1.7 to 3.04 kg, maturity range 32 wks to 40 weeks having congenital cardiac anomalies in 8 cases. One lung (left lung) ventilation by inserting 2.5 to 3mm internal diameter uncuffed Endo Tracheal Tubes (ETT) into left main stem bronchus were used in all cases. Results Out of 12 patients having single lung ventilation, 7 patients (55%) survived. 8 out of 12 (66%) needed ventilator support to a variable extent after surgery. Most of the mortality is due to prematurity, postoperative sepsis and associated congenital anomalies. Conclusion Result of OA surgery is still not encouraging in our country. In a tertiary hospital, we have studied this surgery since 2007. The rate of survival in this hospital is 55%. One lung ventilation is one of the prime factors for this result. So, it should be the choice in any form of oesophageal atresia and tracheoesophageal fistula repair in neonates. JBSA 2012; 25(2): 66-70